Analysis of driving parameters for green flight trajectories - Grande Pardo, J. (author) (2016)
Climate change is an important problem nowadays. There are several industries causing this problem. One of them is the air transport industry. In order to reduce its induced climate impact there are different approaches: design of new aircrafts or engines, use of alternative fuels, more efficient air traffic management, or re-routing. All of them except re-routing aim on reducing carbon dioxide emissions. Re-routing, on the other hand, aims on reducing the climate impact of non-CO2 emissions (that considerably alter their climate impact depending on the region of the atmosphere where they are released) by increasing slightly the carbon dioxide emissions. This study focuses on this last approach. It establishes an analysis of the results obtained within the REACT4C project (Reducing Emissions from Aviation by Changing Trajectories for the benefit of Climate). The project aims to reduce aircraft induced climate impact in the North Atlantic flight corridor by changes in flight trajectories and considers fleets of around 400 aircraft. Moreover, this project considers eight different weather patterns (three for summer and five for winter), two flight directions (westbound and eastbound), and three climate metrics. Therefore, a total of 48 configurations have to be studied. Moreover it considers six different climate parameters causing the total climate impact. The climate parameters are carbon dioxide, water vapor, contrails, and NOx. The NOx climate impact is obtained as the summation of ozone, methane, and primary mode ozone climate impacts. The results that are analyzed are the climate impact caused by each of the climate parameters and how this climate impact changes when applying gradual changes on the aircraft trajectories. The analysis shows that water vapor has a negligible effect on climate impact. Carbon dioxide climate impact is more relevant when considering long term time horizons. Also, it increases when more trajectories are modified since the fuel consumption increases. Contrails are the main driver ...